Associations between diet quality and obesity in a nationally representative sample of Iranian households: A cross‐sectional study - Sara Ebrahimi; Rebecca M. Leech; Sarah A. McNaughton; Morteza Abdollahi; Anahita Houshiarrad; Katherine M. Livingstone (Wiley, 2022)
Abstract Objective Research examining associations between diet quality and obesity in Iranian adults is limited by small and non‐representative samples. This study examined associations between two diet quality indices and obesity risk in a nationally representative sample of Iranian adults and interactions by sex and area of residence. Methods Data on 18,307 adults (mean age 37 [SD 15.2] years) were used from the Iranian National Survey 2001-2003. Two diet quality indices (Healthy Eating Index 2015, HEI‐2015, and Diet Quality Index International, DQI‐I) were calculated from household 24‐h dietary recalls. Multi‐level regression analyses were used to examine the association between household diet quality and individual‐level obesity risk, with interaction terms for sex and area of residence. Results Higher household HEI‐2015 and DQI‐I were associated with higher risk of obesity (HEI‐2015: relative risk ratio: 1.04, 95% CI: 1.03, 1.05; DQI‐I: relative risk ratio: 1.02, 95% CI: 1.01, 1.02), with stronger effect sizes in adults living in rural areas. Conclusions Higher diet quality (HEI‐2015 and DQI‐I) was associated with higher obesity risk, which was stronger in adults living in rural areas. Due to the complexity of examining these associations in a Middle Eastern country undergoing a nutrition transition, longitudinal research is needed to confirm these findings.